Probabilistic Evaluations of Prescribed Safety Margins in Eurocode 7 for Spread Foundations - Ivandić, Krešo; Dodigović, Filip; Soldo, Božo; Kovačević, Meho Saša (Periodica Polytechnica Civil Engineering, 2022)
According to the design code Eurocode 7, analysis procedures require reaching a prescribed safety margin, based on the conditions of levelling design action and design resistance. Such semi-probabilistic procedures do not result in a consistent equivalent value of the Overall Factor of Safety (OFS), neither in individual analysis nor in different tasks in geotechnical engineering. Furthermore, the implementation of different calculation approaches in Eurocode 7 also does not guarantee an equal probability of the occurrence of a relevant limit state. A comparative analysis is conducted for an example of a centrically loaded spread foundation on homogenous, isotropic, and coarse-grained soil, according to procedures in Eurocode 7, Design Approach 3. An algorithm is developed to estimate failure probability, taking into consideration the relevant statistical characteristics of each calculation parameter. A significant influence of the statistical characteristics of the relevant sample is emphasized. The degree of required modification of the equivalent Overdesign Factor (ODF) and the Overall Factor of Safety (OFS), based on the criterion of the required reliability index β and failure probability pf , is quantified.